Penegakan Hak-Hak Alam Di Indonesia Ditinjau Dalam Perspektif Deep Ecology Dan Should Trees Have Standing? - Juniarto Prakoso; Agustinus Supriyanto (Universitas Islam Negeri Islam Kiai Ageng Muhammad Besari Ponorogo, 2026)
Abstract: Environmental protection in Indonesia still relies on an anthropocentric paradigm that positions nature as an object of exploitation, not as an entity with a right to exist. This condition is reflected in various legal instruments, ranging from the 1945 Constitution of the Republic of Indonesia, Law No. 32 of 2009 concerning Environmental Governance, Law No. 41 of 1999 concerning Forestry, to Law No. 6 of 2023 concerning Job Creation, as well as in judicial practices that consistently require direct harm to humans as the basis for a lawsuit. This study aims to analyze the state of enforcement of natural rights in Indonesia and formulate a model for its enforcement through the perspective of